Desperate times call for desperate measures: short-term use of the common ash tree by gypsy moth larvae (Lepidoptera: Erebidae) under density and starvation stress - Milanović, Slobodan D.; Popović, Marija M.; Dobrosavljević, Jovan N.; Kostić, Igor M.; Lazarević, Jelica M. (Archives of Biological Sciences, 2020)
Paper description: Ecological preference of gypsy moth larvae (GML) for non-host ash species increases during insect outbreak. We performed laboratory-feeding trials to assess the conditions that promote short-term use of common ash and the ability of GML to recover from ash ingestion. Growth and consumption were compared between ash fed GML after encountering various density/starvation stresses, and between oak fed and ash-oak switched GML. This is the first report showing that under moderate density/starvation stress GML can temporarily grow on ash leaves and recover after switching to optimal oak leaves. Short-term ash use might give advantage during outbreaks when resources are depleted. Abstract: Gypsy moth, Lymantria dispar L. (Lepidoptera: Erebidae) feeds on a large number of tree species, while ash, Fraxinus spp. (Lamiales: Oleaceae) species are considered resistant and are only sporadically eaten. To assess the conditions under which late instar gypsy moth larvae (GML) can temporarily use non-host common ash (CA) (F. excelsior L.), and to evaluate their ability to recover from ingestion of this toxic food, we determined the relative growth rate, the relative consumption rate and the amount of produced feces in different laboratory feeding trials. Our report is the first to show that under specific circumstances, the resources acquired after short-term consumption of CA leaves can be utilized for larval growth. We varied the intensity of density and starvation stress prior to feeding on CA leaves. We observed that after moderate stress a group of GML was temporarily capable of coping with CA leaves. Although observed growth and consumption were much lower on CA than on the optimal host oak, Quercus cerris L. (Fagales: Fagaceae), CA-oak-switched larvae showed the ability to recover from short-term use of a toxic non-host foliage. This suggests that feeding on CA might enable GML to survive under conditions of food shortage. https://doi.org/10.2298/ABS191106067M Received: November 6, 2019; Revised: November 27, 2019; Accepted: December 16, 2019; Published online: December 30, 2019 How to cite this article: Milanović SD, Popović MM, Dobrosavljević JN, Kostić IM, Lazarević JM. Desperate times call for desperate measures: short-term use of the common ash tree by gypsy moth larvae (Lepidoptera: Erebidae) under density and starvation stress. Arch Biol Sci. 2020;72(1):63-9.